THE ROLE OF THE BODY LANGUAGE IN HUMAN LIFE AND ITS IMPORTANCE IN ORAL TRANSLATION - Arapov Gayrat Namozovich; Ashurova Mohichehra Oybek Qizi (Scholar Express Journal, 2024)
This article provides a brief overview of the role of body language in human life and its importance in oral translation
Keywords: Independent study; pedagogy; body language and oral translation